Reduksi Hak Partisipasi publik Pada Aturan Analisis Mengenai Dampak Lingkungan untuk Perizinan Berusaha di Indonesia: Perspektif Green Constitution - Aditya Prastian Supriyadi (Badan Strategi Kebijakan Hukum, 2023)
The green constitution concept in the Indonesian Constitution is the legal fundamental basis for environmental protection in implementing the national economy through public participation. The rationale for